Can breast cancer be stopped? Modifiable risk factors of breast cancer among women with a prior benign or premalignant lesion. Issue 6 (22nd May 2021) - Lilleborge, Marie; Falk, Ragnhild S; Sørlie, Therese; Ursin, Giske; Hofvind, Solveig
Abstract: Physical inactivity, high postmenopausal body mass index, alcohol consumption and use of menopausal hormone therapy are established risk factors for breast cancer. Less is known about whether these factors influence the risk of progression of benign and premalignant breast lesions to invasive breast cancer. This registry‐based cohort study was based on women with a precancerous lesion who were followed for breast cancer. The cohort consisted of 11 270 women with a benign lesion, 972 women with hyperplasia with atypia and 2379 women with carcinoma in situ diagnosed and treated after participation in BreastScreen Norway, 2006‐2016. Information on breast cancer risk factors was collected by a questionnaire administered with the invitation letter. Cox regression analysis was used to estimate the association between breast cancer and physical activity, body mass index, alcohol consumption, tobacco smoking and menopausal hormone therapy, adjusted for age. During follow‐up, 274 women with a benign lesion, 34 women with hyperplasia with atypia and 118 women with carcinoma in situ were diagnosed with invasive breast cancer. We observed an increased risk of breast cancer associated with use of menopausal hormone therapy for women with a benign or premalignant lesion. Alcohol consumption and tobacco smoking showed suggestive increased risk of breast cancer among women with a benign lesion. We were only to a limited degree able to identify associations between modifiable risk factors of breast cancer and the disease among women with a precancerous lesion, and a larger study is needed to confirm or refute associations. Abstract : What's new? Whether established lifestyle risk factors for breast cancer, such as physical inactivity, use of hormone therapy (HT), and alcohol consumption, fuel cancer development in women with benign or premalignant breast lesions remains uncertain. In this investigation, increased risk of breast cancer development was observed among women with benign breast lesions who used menopausal HT. HT was not significantly linked to premalignant lesions. Likewise, only suggestive associations were detected for alcohol intake, smoking, and physical inactivity in women with benign or premalignant lesions. The findings warrant further study to better understand the impact of lifestyle factors on prior breast lesions.